تأثير الإعلان المؤسساتي على رضا العملاء دراسة ميدانية على عملاء المصارف السورية - المصطفى سامر; سعود نهى (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تناول البحث مفهوم الإعلان المؤسساتي واثر هذا النوع من الإعلان في رضا العملاء، ومحاولة تقديم مقترحات للمصارف السورية تساعدها على اتباع الأسلوب الأفضل للإعلان المؤسساتي الذي يحقق أفضل مستويات رضا من قبل عملائها حيث اعتمد البحث على استخدام أسلوب الإحصاء التحليلي الذي يتناسب مع اهداف الدراسة. كما تمت مراجعة الدراسات والأبحاث السابقة المتعلقة بمتغيرات البحث. وفيما يتعلق بالجانب التطبيقي اعتمد البحث على استبيان لكل من (الإعلان المؤسساتي، رضا العملاء المصرفيين) وبلغ حجم عينة العملاء 210 من عملاء المصارف الخاصة والعامة، وكان من اهم النتائج التي توصل اليها البحث: 1- يوجد علاقة ذات دلالة احصائية بين الإعلان المؤسساتي وبين رضا العملاء المصرفيين. 2- يفسر الإعلان المؤسساتي ما نسبته (43.7%) من تباين رضا العملاء المصرفيين. 3- يوجد تأثير ذودلالة احصائية لنوع الإعلان المؤسساتي المتبع في رضا العملاء المصرفيين. 4- ان الإعلان المؤسساتي الذي يركز على دعم قضية له تأثير معنوي في رضا العملاء المصرفيين، يليه الإعلان الذي يركز على الترويج لصورة إيجابية ومستحبة عن المصرف. The reseearch studied institutional advertising and its effect on clients’ satisfaction. The research gave suggestions to the Syrian banks that help banks choose the most effective type of institutional advertising in order to reach a high level of clients’ satisfaction. Descriptive statics were used to test the hypothesis and to describe the relationship between variables. Previous studies in this field were reviewed. Primary data were collected through conducting a questionnaire on a sample of (210) clients of private and public banks. The questionnaire was to measure both the dependent variable (clients’ satisfaction), and the independent variable (institutional advertising). The research found the following results: 1- There is a statistically significant influence between institutional advertising and clients’ satisfaction. 2- Institutional advertising accounts only to (43.7%) of the changes in the clients’ satisfaction. 3- There is a statistically significant influence of the type of institutional advertising used on clients’ satisfaction. 5- Institutional advertising that supports a cause has the most significant influence on the satisfaction of banks’ clients, followed by institutional advertising that promotes a positive image of the bank.